Typologie des systèmes de culture de coton biologique au Bénin - AZONKPIN, Saturnin; CHOUGOUROU, CHÈPO DANIEL; AGBANGBA, Emile Codjo; Santos, Carline; SOUMANOU, MANSOUROU MOHAMED (My University, 2018)
Understanding growing systems characteristics is relevant for agricultural development. In this context, the present study seeks to identify and characterize the growing systems practised by the producers of Organic Cotton in Benin. To reach this goal, a survey was conducted on a sample of 176 producers. The analysis of the data by Hierarchical classification allowed to identify the growing systems. Their characterization was made according to the farming practices, performance, their frequency in the townships and in the ethnic groups. The results obtained allowed the identification of four growing systems of Organic Cotton: The system of mechanized cultivation with animal traction that does not use new technological packages (S1); the system of manual culture which uses vegetables like previous cropping (S2); the system of mechanized cultivation with animal traction which uses new technological packages (S3) and the system of mechanized cultivation with animal traction which uses new technological packages but continues with the practice of clearing with fire (S4). These systems are distinguished primarily by the variables such as the preparation of the soil, the rotation, the previous cropping, the organic fertilizer, plants insecticides, plants traps and associated cultures. All the producers investigated at Glazoué, Kandi and Sinendé practised respectively the growing systems S2, S1 and S4. Banikoara has, 96,67% of the growers are the system S3 against 3.33% for the system S1. The producers of Ouassa-Péhunco practised at 77.78% the system S3 against 22.22% for the system S1. Respondents of the ethnic groups Adja, Fon and Mahi practised at 100% the system S2. However all Haoussa and Monkolé practised the system S1. Gando, Peulh and Bariba did not practise a system specifically. The system S2 obtained the highest average yield (885,80 ± 36.3 kg/ha). In conclusion, the growing systems vary according to the Common and the ethnic groups. The System S1 was more practised by the producers.
Keywords: Systèmes de culture; coton biologique; pratiques culturales; Bénin; labour mécanisé.